Analysis on the Independent Innovation Path and Development Trend of Emerging Marine Industry Based on DEA Model - Yufeng Liu (Discrete Dynamics in Nature and Society)
The development trend of the emerging marine industry affects the development of the marine economy, to study the independent innovation path of the emerging marine industry and the empirical analysis of its development trend. Based on the independent innovation path of the emerging marine industry, explore the development trend of the emerging marine industry. Select the added value of the emerging marine industry as the dependent variable; R&D personnel and R&D funds as the intermediary variables; innovation efficiency as the explanatory variable; and technical capabilities, technical management capabilities, technical strategies, and network capabilities as control variables, using data packets. The network analysis method establishes a development trend measurement model and analyzes the independent innovation path and development trend of the emerging marine industry through the established model. The four independent innovation paths of technological capability, technological management capability, technological strategy, and network capability have a positive incentive effect on the development of emerging marine industries, and technological capability has a higher incentive for the development of emerging marine industries. Based on the results of empirical analysis, it proposes strategies to promote the development of emerging marine industries, such as enhancing public awareness of emerging marine industries, improving long-term mechanisms for the development of emerging marine industries, and enhancing the independent innovation capabilities of emerging marine industries.